PENGEMBANGAN PERANGKAT PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) POKOK BAHASAN KUBUS dan BALOK - Hotimah, Hosnol; Sunardi, S; Suharto, S (Department of Mathematics Education , University of Jember, 2014)
Abstract. The research aims to know the process and result of development of mathematics learning instrumentswith Cooperative Integrated Reading and Composition (CIRC) model for cube and cuboid topic at eight grade of Junior High School.The purposes of CIRC learning model are improvingstudents ability to understanding mathematic problem solving. Learning instrumentsdevelopment model refers to 4D Thiagarajanmodels which has 4 steps namely define, design, develop, and disseminate.The data of research are obtained by validation sheet, observation sheet of teacher and students activities, questionnaire, and evaluation test.The product of this research are lesson plan, worksheet, student handbook, and evaluation test.The result shows that the learning instruments qualifies validity, practical, and effective criteria. Key Words:4DThiagarajanmodels, Cooperative Integrated Reading and Composition,cube and cuboid.